EVALUACIÓN DE ACTINOMICETOS RIZOSFÉRICOS COMO BIOESTIMULANTE EN PLÁNTULAS DE CACAO (Theobroma cacao L) - Rodriguez Vera, Dennisse Lisbeth (2023)
The present research was conducted with the objective of evaluating rhizospheric actinomycetes as a biostimulant in cocoa (Theobroma cacao L) CCN-51 seedlings. The test was carried out in the Microbiology laboratory of the “La María” Experimental Campus of the State Technical University of Quevedo located at km 7.5 of the Quevedo – El Empalme road. Soil samples were collected in different cantons: Quinindé, Buena Fe and El Empalme. Five actinomycete strains were isolated: T1: GC2; T2: GC3; T3: GC4; T4: BA and T5: EM, which were compared with a control treatment (T6), under a completely randomized design in three repetitions.